Exchange interaction and magnetoresistance in La2/3Ca1/3MnO3 : experiment and models: Сильно коррелированные системы и высокотемпературная сверхпроводимость - Beznosov, A. B.; Belevtsev, B. I.; Fertman, E. L.; Desnenko, V. A.; Naugle, D. G.; Rathnayaka, K. D. D.; Parasiris, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The magnetization M(T) and electrical resistivity r(T) of a La2/3Ca1/3MnO3 film have beenstudied in the temperature range 5 K £ T £ 320 K in the magnetic field intervals10 Oe £ H £ 400 Oe and 0 £ H £ 50 kOe, respectively. It is found that the M(T)/M(0) valueis larger than that predicted by the conventional molecular field model below the Curie point T = 267 K, and that the ln r(T) dependence is close to linear in the temperature range 80 K < T < 200 K (accordingly, &#182 ln r/&#182T is constant in this region). A model of the electrical conductivity and magnetoresistivity of the system describing qualitatively the experimentalresults is proposed (the Dmt model). The model includes a thermally activated (with characteristic energy D) mechanism of conductivity, dependence of the concentration and the effective mass (m) of the itinerant charge carriers on the magnetization, as well as scattering (with characteristic time t) of the charge carriers by static breakings of the translational symmetry, thermal fluctuations of the magnetic order, and phonons.